A prospective multicenter trial on sentinel lymph node biopsy in patients with early-stage cervical cancer (SENTIX). Issue 1 (January 2019) - Cibula, David; Dusek, J; Jarkovsky, J; Dundr, P; Querleu, D; van der Zee, A; Kucukmetin, A; Kocian, R
Abstract : Objective: Sentinel lymph node (SLN) biopsy has been increasingly used in the management of early-stage cervical cancer. It appears in guidelines as an alternative option to systematic pelvic lymphadenectomy. The evidence about safety is, however, based mostly on retrospective studies, in which SLN was combined with systematic lymphadenectomy. Materials and methods: SENTIX is a prospective multicenter trial aiming to prove that less-radical surgery with SLN is non-inferior to treatment with systematic pelvic lymphadenectomy. The primary end point is recurrence rate; the secondary end point is the prevalence of lower-leg lymphedema and symptomatic pelvic lymphocele. The reference recurrence rate was set up conservatively at 7% at 24 months after treatment. With a sample size of 300 patients treated per protocol, the trial is powered to detect a non-inferiority margin of 5% (90% power, p = 0.05) for recurrence rate, 30% reduction in the prevalence of symptomatic lymphocele or lower-leg lymphedema, with reference rates of 30% and 6% at 12 months (p = 0.025, Bonferroni correction). The patients eligible for SENTIX have stage IA1/LVSI+, IA2, IB1 (<2 cm for fertility sparing), with negative LN on pre-operative imaging. Intra-operatively, patients are excluded when there is a failure to detect SLN on both sides of the pelvis in cases of more advanced cancer (stage >IB1), or a positive intra-operative SLN assessment. The quality of SLN pathology evaluation will be assessed by central review. Three interim safety analyses are pre-planned when 30, 60, 150 patients complete 12 months' follow-up. Conclusions: The first patient was enrolled into the study in June 2016 and, by June 2018, 340 patients had been enrolled. The first analysis of secondary outcomes should be available in 2019 and the oncological outcome of 300 patients at the end of 2021. The trial is registered as a CEEGOG trial (CEEGOG CX-01), ENGOT trial (ENGOT-Cx 2), and at the ClinicalTrials.gov database (NCT02494063).